An Advanced Framework for Merging Remotely Sensed Soil Moisture Products at the Regional Scale Supported by Error Structure Analysis: A Case Study on the Tibetan Plateau - Jian Kang; Rui Jin; Xin Li (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing, 2021)
Data fusion can effectively improve the accuracy of remotely sensed (RS) soil moisture (SM) products. Understanding the error structures of RS SM products is beneficial for formulating a data fusion scheme. In this article, a data fusion scheme is examined on the Tibetan Plateau, and the Soil Moisture Active Passive mission, Soil Moisture and Ocean Salinity mission, and Advanced Microwave Scanning Radiometer 2 products are used as the experimental input datasets. The RS apparent thermal inertia (ATI) is transformed into SM values as the reference data with reliable systemic variability. The ATI-based SM, along with three RS SM products, is introduced into the triple collocation (TC) method to decompose the errors of the three RS SM products into systemic and random errors at each RS pixel. Due to the presence of systemic errors, the temporal mean values and amplitudes of the three RS SM products were calibrated by those of the ATI-based SM. The rescaled anomalies (including amplitude and random error) were merged according to their random errors estimated by the TC method, and then the merged anomalies were added to the temporal mean values of the ATI-based SM to obtain the final merged results. Compared with the merged European Space Agency Climate Change Initiative passive SM product and input SM datasets, the merged results in this article exhibit optimal accuracy. The scheme for merging RS SM products shows high data fusion performance and can be further considered a reliable way to obtain a high-quality merged RS SM dataset.